1990
DOI: 10.1007/bf01245023
|View full text |Cite
|
Sign up to set email alerts
|

Light affects neonatal rat pineal gland N-acetyltransferase activity by an extra-retinal mechanism

Abstract: To determine whether extra-retinal mechanisms mediate photoperiodic changes in neonatal rat pineal gland N-acetyltransferase activity, 4-day-old intact or bilateral orbital enucleated rats were killed during the dark phase of the lighting cycle, either in darkness or following 4 hr exposure to fluorescent light. Light suppressed the high nighttime N-acetyltransferase activity equally in intact and enucleated pups. Subsequent studies showed that at least 0.5 hr exposure and nocturnal illuminances of 109 microW/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
8
0

Year Published

1994
1994
2003
2003

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 24 publications
2
8
0
Order By: Relevance
“…Certain other rod and cone-specific phototransduction components, however, are absent from the pineal. Our findings support other evidence indicating that mammalian pineal glands are physiologically photosensitive in early life (Zweig et al, 1966;Machado et al, 1969a,b;Wetterberg et al, 1970;Torres and Lytle, 1990) and fit with known features of retina and pineal development. The eyes of a rat do not open until the third week of life, so that at earlier stages the pineal gland, which is located quite superficially underneath the very thin neonatal skull, receives more incident light than the retina (Torres and Lytle, 1990).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Certain other rod and cone-specific phototransduction components, however, are absent from the pineal. Our findings support other evidence indicating that mammalian pineal glands are physiologically photosensitive in early life (Zweig et al, 1966;Machado et al, 1969a,b;Wetterberg et al, 1970;Torres and Lytle, 1990) and fit with known features of retina and pineal development. The eyes of a rat do not open until the third week of life, so that at earlier stages the pineal gland, which is located quite superficially underneath the very thin neonatal skull, receives more incident light than the retina (Torres and Lytle, 1990).…”
Section: Discussionsupporting
confidence: 92%
“…Findings that neonatal pinealocytes show photoreceptor-like differentiation in vivo (Zimmerman and Tso, 1975) and in vitro (Araki, 1992) favor direct detection of light by neonatal rat pineal. Regulation of the melatonin-forming enzyme serotonin N-acetyltransferase (NAT) has been demonstrated in blinded neonatal rats in some studies (Torres and Lytle, 1990), but not in others (Deguchi, 1982b;Reppert et al, 1984). It has not proved feasible to demonstrate light-induced electrophysiological changes in dissociated rat pinealocytes nor modulation of melatonin production in neonatal pineal cultures (Brammer and Binkley, 1981).…”
mentioning
confidence: 99%
“…This form of extraocular photoreception disappears after about 6 days of age (Torres and Lytle 1990). There is evidence to suggest that the neonatal rat pineal gland contains photoreceptors particularly sensitive to blue light (Blackshaw and Snyder 1997).…”
Section: Extraocular Light and Reentrainment 811mentioning
confidence: 96%
“…Torres and Lytle (5,6) showed that exposing blinded neonatal rats to light during the subjective night significantly reduced the activity of the melatonin-forming enzyme arylalkylamine N-acetyltransferase (AA-NAT). Sympathectomy of neonatal rat pineal does not interfere with light entrainment of pineal melatonin in the first weeks of life, whereas sympathectomy at later postnatal ages abolishes light entrainment (7,8).…”
mentioning
confidence: 99%